DEPsy Model / Che Norhalila Che Mohamed and Nora Mohd Basir - Che Mohamed, Che Norhalila; Mohd Basir, Nora (Faculty of Computer and Mathematical Sciences, 2023)
Depression is one of the most common mental disorders, affecting most people directly or indirectly in their lives, including university students. Assessment methods and factors contributing to depression have been consistently studied throughout to improve the life of a university student. However, a continuous and independent monitoring method has not yet been developed. Therefore, this innovation was developed to puts the power of mental health assessment firmly into the hands of university students by considering several common causes of depression, including demographics, academic performance, finances, and social support. A cross-sectional study was conducted on a sample of university students in Negeri Sembilan using a stratified sampling method that consisted of 370 students as a sample. The students need to complete the survey, which measures the variables stress (Inventory of College Students’ Recent Life Experiences), depressive symptoms (Center for Epidemiologic Studies Depression Scale), and social support (Multidimensional Scale of Perceived Social Support). This model was created using the multiple linear regression method to estimate the depression symptoms of the students. This innovation serves as a light hope for university students in monitoring their depression symptoms. This encourages a proactive and healthy culture for the student to act immediately at the first sign of depression, such as doing recreational activities, having counseling sessions, and taking a healthy diet. This innovation is not only beneficial to the student for better mental health outcomes, improved academic performance, and a more positive university experience but also translates into university management that prepares a healthier campus environment and a strong reputation for prioritizing student well-being. These potential benefits work together to create a community where students can succeed academically and emotionally.